2022
DOI: 10.1155/2022/8965280
|View full text |Cite|
|
Sign up to set email alerts
|

Social Media Analytics for Pharmacovigilance of Antiepileptic Drugs

Abstract: Epilepsy is a common neurological disorder worldwide and antiepileptic drug (AED) therapy is the cornerstone of its treatment. It has a laudable aim of achieving seizure freedom with minimal, if any, adverse drug reactions (ADRs). Too often, AED treatment is a long-lasting journey, in which ADRs have a crucial role in its administration. Therefore, from a pharmacovigilance perspective, detecting the ADRs of AEDs is a task of utmost importance. Typically, this task is accomplished by analyzing relevant data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Many of the publications state that similar patterns of adverse events were reported in social media as compared to other traditional pharmacovigilance data sources [35-43, 47, 48, 51-56, 60-62, 64-70, 74-78, 82, 83, 85-89, 92, 94, 98, 99, 102-105]. However, some studies [24,45,46,50,57,59,62,89,94,102,103] detected fewer numbers of adverse events on social media.…”
Section: Results Of Comparisonmentioning
confidence: 88%
See 2 more Smart Citations
“…Many of the publications state that similar patterns of adverse events were reported in social media as compared to other traditional pharmacovigilance data sources [35-43, 47, 48, 51-56, 60-62, 64-70, 74-78, 82, 83, 85-89, 92, 94, 98, 99, 102-105]. However, some studies [24,45,46,50,57,59,62,89,94,102,103] detected fewer numbers of adverse events on social media.…”
Section: Results Of Comparisonmentioning
confidence: 88%
“…A further seven studies [21, 24,45,50,55,56,81,95] used third party software to detect or extract ADE mentions. For 17 studies [48,51,58,64,65,69,70,75,80,82,83,85,94,97,98,[102][103][104][105]] some methodological issues were identified such as (1) lack of reproducibility [45], (2) no mention of manual validation of ADE mentions [58,85], (3) missing key information such as the volume of social media data from which the ADE signals were extracted or analysed [70][71][72], and (4) using lexical match for ADE detection or extraction [43,48,50,58,64,69,86,89,93,98]. For the remaining 29 studies [36-43, 46, 47, 49, attempted to remove non-personal accounts (such as organizations or companies).…”
Section: Methods Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%